2017
DOI: 10.1063/1.5003195
|View full text |Cite
|
Sign up to set email alerts
|

Conduction band fluctuation scattering due to alloy clustering in barrier layers in InAlN/GaN heterostructures

Abstract: In InAlN/GaN heterostructures, alloy clustering-induced InAlN conduction band fluctuations interact with electrons penetrating into the barrier layers and thus affect the electron transport. Based on the statistical description of InAlN compositional distribution, a theoretical model of the conduction band fluctuation scattering (CBFS) is presented. The model calculations show that the CBFS-limited mobility decreases with increasing two-dimensional electron gas sheet density and is inversely proportional to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Polar optical phonon (POP) scattering is the dominant scattering mechanism in 2DEG in GaN‐based heterostructures at temperatures above 200 K. [ 6,7 ] Only the phonons around the Brillouin‐zone center contribute to electron scattering to satisfy momentum conservation. These phonons have a constant energy of ω 0 = 91.2 meV $�?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polar optical phonon (POP) scattering is the dominant scattering mechanism in 2DEG in GaN‐based heterostructures at temperatures above 200 K. [ 6,7 ] Only the phonons around the Brillouin‐zone center contribute to electron scattering to satisfy momentum conservation. These phonons have a constant energy of ω 0 = 91.2 meV $�?…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The higher 2DEG density of InAlN/GaN heterostructures allows HEMT devices to achieve higher output power, however, it may also result in the migration of more electrons from the lowest subband to higher subbands. SdH lowtemperature measurements of InAlN/GaN heterostructures have demonstrated that the 2DEG density of subband 2 exceeds 5% of the total 2DEG density at 0.28 K. [5] As the temperature increases, the proportion of electrons occupying higher subbands steadily increases.Polar optical phonon (POP) scattering is the dominant scattering mechanism in 2DEG in GaN-based heterostructures at temperatures above 200 K. [6,7] Only the phonons around the Brillouin-zone center contribute to electron scattering to satisfy momentum conservation. These phonons have a constant energy of ℏω 0 ¼ 91.2 meV, [8] which is within the same order of magnitude as the electron energy.…”
mentioning
confidence: 99%